2013
DOI: 10.1111/itor.12004
|View full text |Cite
|
Sign up to set email alerts
|

Using decomposition to improve greedy solutions of the optimal diversity management problem

Abstract: The optimal diversity management problem is a special case of the p‐median problem, which arises in the production of wire harness for the automotive industry. Instances are typically very large and graphs consist of several nonconnected components. The greedy algorithm is normally applied to handle these large instances, producing solutions that are considered quite good. We design an approach that uses decomposition combined with a genetic algorithm and simulated annealing algorithm to improve greedy solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In [2] it is observed that the values q U k obtained with the greedy algorithm are close to the ones from optimal solutions, i.e., the greedy solution gives a good estimate of the optimal number of facilities to choose from each subgraph G k . Based on this observation, matrix U is further refined in a neighborhood of values q U k using a relax-and-fix heuristic as follows.…”
Section: Initial Upper Boundsmentioning
confidence: 86%
See 1 more Smart Citation
“…In [2] it is observed that the values q U k obtained with the greedy algorithm are close to the ones from optimal solutions, i.e., the greedy solution gives a good estimate of the optimal number of facilities to choose from each subgraph G k . Based on this observation, matrix U is further refined in a neighborhood of values q U k using a relax-and-fix heuristic as follows.…”
Section: Initial Upper Boundsmentioning
confidence: 86%
“…We address the p-median problem when graph G has several different connected components. This case arises in the automotive industry, namely in the production of electric wiring configurations for vehicles, where the problem is known as the optimal diversity management problem [1,2,4,5,6]. This situation also occurs when location takes place over split administrative regions or regions geographically apart (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A decomposition approach was also proposed in where p ‐median heuristics and a MCKP dynamic programming algorithm were developed, taking into account the particularity of ODMP instances. Recently, the same authors proposed an exact approach using LP relaxation bounds for sub‐PMP s and variable fixing in MCKP to reduce the number of sub‐PMP s to be solved .…”
Section: Literature Reviewmentioning
confidence: 99%